Elaboración de un prototipo de tela vinílica recubierta a escala laboratorio empleando PVC y plastificante bioatribuido para la Empresa Proquinal S.A.S (2023)
The development of new products that have a lower impact on the carbon footprint is a challenge for the global manufacturing industry. In the case of textile industries, polyvinyl chloride, a substance from petrochemical derivatives, is used in their processes. The present work seeks to reduce the consumption of non-renewable materials, developing a coated vinyl fabric that associates biodegradable molecules as a substitute for the polyvinyl chloride and the plasticizer used conventionally, for this the substitution of these raw materials was used depending on the substitution factor within the formulations of line products in the company Proquinal S.A.S; The layer, foam and lamination were evaluated using Severs and Brookfield viscosity, methods used to analyze rheological and process behaviors, this being a critical selection factor.